EKSEKUSI JAMINAN KREDIT BERUPA KIOS PASAR OLEH BANK - Hardianto, Tri; Nasution, Krisnadi; Setiadji, Sri (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
The bank is an intermediary institution, meaning that its main activities are raising funds and channeling funds to the public. The funds withdrawn from the community are then channeled back to the community in the form of credit. Lending is generally done by entering into an agreement. "The agreement consists of a principal agreement, namely a debt and credit agreement and is followed by an additional agreement in the form of a guarantee agreement by the debtor. One object commonly used as collateral in a credit agreement is a market stall. The problem in this research is how the legal status of market kiosk ownership is used as a credit guarantee by the bank and how the bank's position in executing the credit guarantee is in the form of a market kiosk if the debtor defaults. In terms of the market stall material law cannot be categorized as an object because the market stall is only a permit to use the building, it cannot give birth to material relations even though the debtor has a permit in the form of a certificate of use of the right to sell in the form of KBP, SPTU, BPTU or type of permit to use the market stall others from the local government. Traders only have the right to lease or the right to use the market stall they occupy, the trader is not the owner. Until now because there are no regulations governing the mechanism of execution of credit guarantees in the form of market kiosks, execution of credit guarantees by binding under the form of market kiosks is carried out by asking the assistance of the market head or the market manager authorized to carry out the takeover of these market kiosks. transferred (leased) to other parties who intend to rent the kiosk.